Tindak Pidana Dan Pertanggungjawaban Pidana Terhadap Seseorang Yang Mengetahui Di Sekitar Lingkungannya Terdapat Tindak Pidana Narkotika (Studi Putusan Pengadilan Negeri Sibolga No: 17/Pid.B/2014/PN.Sbg) - Zulfikar Lubis; Alfi Syahrin; Mahmud Mulyadi; Marlina Marlina (Iuris Studia: Jurnal Kajian Hukum, 2021)
One of the narcotics criminal acts which is quite interesting to study is someone who knows that there is a narcotics crime as regulated in Article 131 of Law No. 35 of 2009 concerning Narcotics. Therefore, it is necessary to study the criminal act of Article 131 of Law No. 35 of 2009 concerning Narcotics, the criminal responsibility of a person who knows that there is a narcotics crime in the vicinity of the crime and the reason for eliminating the crime against someone who knows that there is a narcotics crime around his environment